Impact and Sustainability of Regional Development Center Point of Indonesia Makassar - Haeruddin Saleh; Agus Salim; Zulkifli Maulana; Rahmaniah Rahmaniah; Darmawati Manda (STMIK Dharma Wacana, 2023)
This study aims to understand changes in spatial structure and spatial patterns in the coastal area in the Makassar urban system due to land use conversion. This study uses a qualitative approach, by collecting data through observation, visual analysis, literature study, interviews, and documentation. The results of the study show that changes in spatial use in the Center Point of Indonesia area have led to the marginalization of local communities. Intensive land conversion has changed the work system of local communities, replacing them with the urban industrial community work system. The orientation of the development of the Center Point of Indonesia area is to create business opportunities for people engaged in the informal sector, tourism, transportation, and other service sectors, as well as create a friendly and modern environmental area. Overall, this beach reclamation has a positive impact on the environment that is sustainable and provides business opportunities and increased income for the community